Identifikasi Endapan Batuan Volkanik Berdasarkan Data Sistem Informasi Geografi (SIG) Daerah Danau Ranau, Propinsi Sumatera Selatan - ., Idarwati (PROMINE, 2015)
Ranau Lake as the second biggest lake in Sumatra Island. On Plio-Pleistocene Ranau Volcano (Volcano-tectonic) eruption resulted the formation of Ranau Lake. After the great eruption of Ranau Volcano, grow up another volcanoes like Seminung Volcano, and become a Ranau Volcanic Complex. At the foot of Seminung Volcano often showed sulfur gas burst activity which are indicated by the death of organism in Ranau Lake. The increasing of burst gas and locally earthquacke to be the principle one to predict the possibility of volcano eruption for anticipation and decrease the impact of volcano eruption. The research objective was to determain the characteristics of rocks formation surrounding Ranau Lake using Landsat Imagery.      Keywords: Ranau Lake, Volcano, Landsat Imagery.